Kinetics and mechanism of oxidation of cetirizine hydrochloride, an anti-allergy agent by Mn(VII) in acidic medium - Panda, J.; Patnaik, Ajaya Kumar; Pradhan, G. C.; Mohanty, P. (International Journal of Advanced Chemistry, 2014)
The kinetics and mechanism of oxidation of cetirizine hydrochloride by Mn(VII) in acidic medium was studied spectrophotometrically. The electron transfer reaction between MnO4- and the drug have been studied over the range 2.0 ? 103 [cetirizine hydrochloride] ? 6.0, 2.5 ? pH ? 4.5 and 295 K ? T ? 313 K in aqueous medium. The electron transfer reaction shows first order dependence in [MnO4-] T and [cetirizine hydrochloride]. The rate of the reaction was found to increase with increasing pH of the medium. The conjugate base of the reactant drug and MnO4- reacts to produce products. The activation parameters ?H? (kJ mol-1) and ?S? (JK-1 mol-1) for the electron transfer reaction was found to be 33.93 and -143.00. The product of the reaction was cetirizine N-oxide. Keywords: Cetirizine, Oxidation, Kinetics, Cetirizine N-Oxide, Spectrophotometer.